Biological effects of active fraction isolated from Hydnocarpus pentandra (Bunch. –Ham.) Oken seeds against Helicoverpa armigera (Hub.) (Lepidoptera: Noctuidae). (3rd April 2017) - Sivaraman, Govindan; Paulraj, Michael Gabriel; Balakrishna, Kedike; Stephen Irudayaraj, Santiagu; Ignacimuthu, Savarimuthu; Al-Dhabi, Naif Abdullah
Abstract: Hexane, chloroform, ethyl acetate and methanol extracts of Hydnocarpus pentandra (Flacourtiaceae) seeds were tested for antifeedant, larvicidal, pupal mortality and adult deformations activities against Helicoverpa armigera. Crude extracts were screened at 0.5, 1.0, 1.5 and 2.0% concentrations. Bioassay-guided fractionation method was followed to isolate the active fraction from the crude extract. Active fraction was analysed by FT-IR, 1 H NMR, 13 C NMR and GC-MS. Hexane extract presented the highest antifeedant (87.89%), pupal mortality (41.67%) and adult malformation activities at 2% concentration. Seven different fractions were isolated from hexane extract, among which fraction-2 showed the highest antifeedant (81.43%) activity and recorded the lowest LC50 of 792.07 ppm. The fraction-2 contained two cyclopentenyl carboxylic acids, such as hydnocarpic acid (1) and chaulmoogric acid (2) in the ratio of 2:1. These compounds were major constituents in the active fraction of hexane extract of H. pentandra seeds. Fraction-2 can be used for agricultural pest management.